Modified Shock Index as Simple Clinical Independent Predictor of In-Hospital Mortality in Acute Coronary Syndrome Patients: A Retrospective Cohort Study - Pramudyo, Miftah; Marindani, Vani; Achmad, Chaerul; Putra, Iwan Cahyo Santosa (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Despite being the current most accurate risk scoring system for predicting in-hospital mortality for patients with acute coronary syndrome (ACS), GRACE risk score is time consuming due to the requirement for electrocardiography and laboratory examinations. This study aims to evaluate the association between modified shock index (MSI), as a simple and convenient index, with in-hospital mortality and revascularization in hospitalized ACS patients. Methods: A single-centered, retrospective cohort study, involving 1393 ACS patients aged ≥18 years old was conducted between January 2018 to January 2022. Study subjects were allocated into two cohorts: high MSI ≥1 (n=423) and low MSI <1 group (n=970). The outcome was in-hospital mortality and revascularization. The association between MSI score and interest outcomes was evaluated using binary logistic regression analysis. The area under the curve (AUC) between MSI and GRACE score was compared using De Long's method. Results: MSI ≥1 had 61.1% sensitivity and 73.7% specificity. High MSI score was significantly and independently associated with in-hospital mortality in ACS patients [OR=2.72(1.6-4.58),p<0.001]. However, STEMI and NSTEMI patients with high MSI did not significantly increase the probability of revascularization procedure. Receiver operating characteristic (ROC) analysis demonstrated although MSI and GRACE scores were both good predictors of in-hospital mortality with the AUC of 0.715(0.666-0.764) and 0.815(0.775-0.855) respectively, MSI was still inferior compared to GRACE scores in predicting mortality risk in ACS patients (p<0.001). Conclusion: MSI, particularly with a score ≥1, was a useful and simple parameter for predicting in-hospital mortality in patients presenting with ACS. Keywords: modified shock index, global registry of acute coronary events score, acute coronary syndrome, in-hospital mortality, revascularization